(2E)-1-(2,5-Dimethoxyphenyl)-3-(3-nitrophenyl)prop-2-en-1-one - Fun, Hoong-Kun (International Union of Crystallography, 2011)
In the title compound, C(17)H(15)NO(5), an intramolecular C—H⋯O hydrogen bond generates an S(6) ring motif. The benzene rings form a dihedral angle of 6.45 (7)° with each other. In the crystal, inversion dimers linked by pairs of C—H⋯O hydrogen bonds generate R (2) (2)(8) loops. Adjacent dimers are further connected by C—H⋯O hydrogen bonds into an infinite chain along the [011] direction.